Students' Creative Thinking Indicators in Solving Open-Ended Problems Across Different Levels of Mathematical Ability - Maifa Munsyaila Putri; Rohati Rohati; Duano Sapta Nusantara (MASI Mandiri Edukasi, 2026)
Previous studies have examined mathematical creative thinking in open-ended problem solving; however, qualitative investigations that explicitly trace the emergence of each creative thinking indicator — fluency, flexibility, originality, and reasoning depth — across different mathematical ability levels remain limited. Departing from the traditional elaboration indicator, this study adopts reasoning depth to more accurately capture students' process-oriented mathematical reasoning, representing a conceptual novelty in the assessment framework applied. This study aims to describe how students' mathematical creative thinking indicators emerge in solving open-ended problems based on mathematical ability. A descriptive qualitative approach was employed with six students from SMA Negeri 14 Kota Jambi, Indonesia, representing high, medium, and low mathematical ability levels. Data were collected through written tests and semi-structured interviews and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that mathematical ability shapes students' creative thinking profiles but does not guarantee the development of all indicators. Fluency and reasoning depth emerged more consistently among high-ability students, while originality remained the most constrained indicator across all groups, regardless of ability level. Medium-ability students showed inconsistent indicator emergence, whereas low-ability students exhibited limited development across all four indicators. These findings imply the need for instructional designs that integrate open-ended tasks with strategies explicitly promoting divergent thinking, strategic flexibility, and reflective reasoning across all ability levels.